M-Lotka-Volterra type operators - Mukhamedov, Farrukh; Saburov, Mansoor (National University of Uzbekistan Press, 2009)
In this paper we study Lotka-Volterra type operators defined in finite dimensional simplex. We intorduce notions of M-Lotka-Volterra type operators and we study limit behavior of trajectory such kind of operators.